Iconography of the modernization of the Spanish education system in the context of the General Education Law of 1970 - González Gómez, Sara; Motilla Salas, Xavier (Historia y Memoria de la Educación, 2018)
Spain’s General Education Law (Ley General de Educación) of 1970 meant the introduction of a new heterogeneous legislative framework that combined, on the one hand, the traditional educational policies of the government, and on the other, a renewed, innovative ethos inspired by the international educational reforms that had been taking place since the 1960s. The main objective of this article is to analyze whether or not the modernization of the Spanish education system that began in the context of the 1970 reform could be seen in the visual discourse created by the Franco regime. We try to ascertain to what extent the government would have wanted to transmit, for propagandistic purposes, an image of the modernization of the education system in national and foreign media, and what levels of education were used to exploit this iconography through an analysis of the collection of photographs compiled for dissemination by the Spanish news agency Agencia EFE.